Biological Treatments: New Weapons in the Management of Monogenic Autoinflammatory Disorders. (21st July 2013) - Vitale, Antonio; Rigante, Donato; Lucherini, Orso Maria; Caso, Francesco; Muscari, Isabella; Magnotti, Flora; Brizi, Maria Giuseppina; Guerrini, Susanna; Patti, Maria; Punzi, Leonardo; Galeazzi, Mauro; Cantarini, Luca
Abstract : Treatment of monogenic autoinflammatory disorders, an expanding group of hereditary diseases characterized by apparently unprovoked recurrent episodes of inflammation, without high-titre autoantibodies or antigen-specific T cells, has been revolutionized by the discovery that several of these conditions are caused by mutations in proteins involved in the mechanisms of innate immune response, including components of the inflammasome, cytokine receptors, receptor antagonists, and oversecretion of a network of proinflammatory molecules. Aim of this review is to synthesize the current experience and the most recent evidences about the therapeutic approach with biologic drugs in pediatric and adult patients with monogenic autoinflammatory disorders.